2004
DOI: 10.1124/dmd.104.002444
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolism of Polychlorinated Biphenyls and Tissue Distribution of Persistent Metabolites in Rats, Hamsters, and Guinea Pigs

Abstract: ABSTRACT:The present study was performed to compare the metabolite profiles of polychlorinated biphenyls (PCBs) in the liver and serum of rats, hamsters, and guinea pigs after exposure to a PCB mixture, Kanechlor 500 (100 mg/kg, i.p.). The percentage of contribution of major PCB residues in the liver 5 days after exposure indicated that nonplanar PCBs with 2,4-or 2,3,4-chlorine substitution were more abundant in the liver in the order rats (43% of total PCBs) > hamsters (20%) > guinea pigs (11%), whereas copla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 37 publications
0
17
0
5
Order By: Relevance
“…These results indicate the meta-position of the 2,5-chlorine-substituted phenyl ring, whereas the para-position of the 2,3,6-chlorinesubstituted phenyl ring in the molecule is the preferred site for methylsulfonylation, and fish may have substrate-specific phase II isozymes that catalyze the nucleophilic reaction of arene oxide intermediates with sulfhydryl groups. Feeding studies with rats exposed to PCBs also showed that 2,5-chlorine-substituted PCBs produced more meta-MeSO 2 -PCBs than paraMeSO 2 -PCBs, whereas 2,3,6-chlorine-substituted PCBs had the opposite metabolic deviation [18,31,32]. However, a different pattern for MeSO 2 -PCB 132, a congener with 2,3,6-chlorine substitution, was observed between the mud carp and northern snakehead.…”
Section: Congener Profiles Of Meso 2 -Pcbsmentioning
confidence: 90%
“…These results indicate the meta-position of the 2,5-chlorine-substituted phenyl ring, whereas the para-position of the 2,3,6-chlorinesubstituted phenyl ring in the molecule is the preferred site for methylsulfonylation, and fish may have substrate-specific phase II isozymes that catalyze the nucleophilic reaction of arene oxide intermediates with sulfhydryl groups. Feeding studies with rats exposed to PCBs also showed that 2,5-chlorine-substituted PCBs produced more meta-MeSO 2 -PCBs than paraMeSO 2 -PCBs, whereas 2,3,6-chlorine-substituted PCBs had the opposite metabolic deviation [18,31,32]. However, a different pattern for MeSO 2 -PCB 132, a congener with 2,3,6-chlorine substitution, was observed between the mud carp and northern snakehead.…”
Section: Congener Profiles Of Meso 2 -Pcbsmentioning
confidence: 90%
“…The [ 125 I]T 4 , radiolabeled at the 5Ј-position of the outer ring, was obtained from PerkinElmer Life and Analytical Sciences (Waltham, MA). The KC500 used in the present experiments contains 2,2Ј,5,5Ј-tetrachlorobiphenyl (5.6% of total PCBs), 2,2Ј,3,5Ј,6-pentachlorobiphenyl (6.5%), 2,2Ј,4,5,5Ј-pentachlorobiphenyl (10%), 2,3,3Ј,4Ј,6-pentachlorobiphenyl (7.4%), 2,3Ј,4,4Ј,5-pentachlorobiphenyl (7.7%), 2,2Ј,3,4,4Ј,5Ј-hexachlorobiphenyl (5.6%), and 2,2Ј,4,4Ј,5,5Ј-hexachlorobiphenyl (5.4%) as major PCB congeners (Haraguchi et al, 2005). All the other chemicals used herein were obtained commercially in appropriate grades of purity.…”
Section: Methodsmentioning
confidence: 99%
“…These electrophilic species are known to interact with electrons of chlorinated aromatic compounds (Vrtacnik and Voda, 2003), yielding different hydroxylated and dechlorinated oxidation products (Liu et al, 2009). In vivo, dechlorination reactions have been described for several polychlorinated hydrocarbons, such as the polychlorinated biphenyls (Schnellmann et al, 1984;Ariyoshi et al, 1997;Haraguchi et al, 2005). The mechanism presumably proceeds via an epoxidation of TCC by P450 TCC or 3Ј,4Ј-epoxy TCC, followed by a dechlorination to 3,4-dichloro 4Ј-hydroxycarbanilide, as discussed by Ariyoshi et al (1997) for the metabolism of polychlorinated biphenyl 153.…”
Section: Electrochemical Studies Of Tcc Show Reactive Metabolitesmentioning
confidence: 99%